Compliance with Iron and folic acid supplementation (IFAS) and associated factors among pregnant women: results from a cross-sectional study in Kiambu County, Kenya - Mary Wanjira Kamau; Waithira Mirie; Samuel Kimani (BMC, 2018)
Abstract Background Macro and micronutrients including iron and folic acid deficiencies are prevalent in Kenya, particularly during pregnancy resulting in anaemia. Despite efforts to control anaemia in pregnancy by adopting Iron and Folic Acid Supplementation (IFAS), this public health problem has persisted contributing to significant morbidity and mortality. The problem notwithstanding, there is poor IFAS compliance, whose reasons remain poorly understood, calling for their investigations. We sought to determine compliance status with IFAS and associated factors among pregnant women. Methods This was a cross-sectional study involving 364 pregnant women aged 15-49 years. Using two stage cluster sampling, one Sub-County and five public health facilities in Kiambu County were selected. All pregnant women attending antenatal clinics who met inclusion criteria and consented to participate in the study were recruited. Compliance with IFAS was defined as taking supplements at least 5 out of 7 days per week. A structured interviewer-administered questionnaire consisting of sociodemographic data, IFAS maternal knowledge and compliance practices was pretested and administered. Descriptive and inferential statistics were computed using STATA. Results Of the 364 respondents interviewed, 32.7% were IFAS compliant and 40.9% scored high on its knowledge. Of those with high IFAS knowledge, 48.3% were compliant compared to those with low knowledge (21.4%, n = 46, PR = 2.25;95%CI = 1.59-3.17, p < 0.001). Women who were multigravid (30.4%) were less likely to comply compared to primigravid (37.2%, n = 45, PR = 0.68;95%CI = 0.47-0.99, p = 0.004). Multivariate analysis revealed that respondents counselled on management of IFAS side effects (100%, n = 4) were more compliant (76.2%, n = 112, aPR = 1.31;95%CI = 1.19-1.44, p < 0.001). Conclusion Few pregnant women were compliant with IFAS regimen, associated with: knowledgeability on IFAS, primi-gravidity, and IFAS counselling especially on management of its side effects. These underscore the need for approaches to scale up health awareness on the benefits of IFAS, mitigation measures for the side effects, as well as targeted counselling.